KELOMPOK BELAJAR "KANCIL" SEBAGAI UPAYA PEMENUHAN HAK PENDIDIKAN ANAK PENJUAL KRESEK DI PASAR UJUNGBERUNG (Sosio Konsepsia, 2010)
Child plastic bag seller community in Ujzmgberzmg traditional market is one of the social phenomena that indicate that child's condition is not yet fully prosper. Such children can be categorized as a child labor. In their growth period they should get their right in accordance to their development stage, one of which is the right to get proper education. In 2009 the number of the children in this community reached 35 children. Among this child, 13 of them are classified as most vulnerable. From this most vulnerable classification, 8 children have dropped out of school and 5 children still attending school. The condition of this child plastic bag seller community showed that children's right, especially right to proper education still not optimallyfulfilled. This condition will affect their future. Given that children are our next generation, then we must prepare their future as best as we can. After the assessment is done, these problem then arises a special need, a need for a place to learn together in the fonn of study group, the study group they later name as "kancil" The function of this study group is as a place to learn to prepare those who dropped out of school to take equation test and to help those who still attending school to do their homework/schoolwork, the limited ability and knowledge of the families of this children is the main cause for their inability to learn at home.